DELAYED REPLANTATION OF AVULSED TOOTH WITH 22 HOURS DRY TIME: FOUR YEARS FOLLOW-UP OF A VIABLE TREATMENT MODALITY - Ulfat, Hamza; Javed, Muhammad Qasim; Haq, Sabana (Journal of Ayub Medical College Abbottabad, 2021)
Avulsion is the complete displacement of tooth out of its socket. It is the gravest form of dental traumatic injury which accounts for 0.5-3% of the total dental traumatic injuries of the permanent teeth and most commonly involves the maxillary central incisors. The treatment is immediate tooth replantation or if that is not possible then storing tooth in an appropriate storage medium and attending dental clinic at the earliest. The present case report describes the replantation of maxillary left central incisor tooth that was avulsed. The tooth was out of the socket for 22 hours without any storage medium. Tooth was replanted after the removal of non-viable periodontal tissues; splinting was done for 4 weeks and endodontic treatment was initiated after 7 days. The tooth was stable and functional with mild discoloration and ankyloses at four years follow up, which is considered a desirable treatment outcome after delayed replantation.